Dynamics of collaborative invention tracking growth of cooperative and total patents in the region - Matthias Bürger (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
The paper targets the relationship between growth of cooperation and later growth of innovation at the regional level. Patent data for German regions and eleven subsequent years is used to identify collaborative activity as well as the innovative output in each region. The results confirm to some extend previous expectations based on the assumption of an inverted U-relationship. Depending on the regional level of cooperation there are positive and negative effects of a change in regional cooperation behaviour in the industries Radio, Television and Communication Equipment and Machinery and Equipment. No significant results are obtained for the industries Chemicals and Chemical Products as well as Medical, Precision and Optical Instruments.
Keywords: O18; R11; 330; regional innovativeness; cooperation; regional growth; Regionales Wachstum; Innovation; Unternehmenskooperation; Forschungskooperation; Patent; Branchenentwicklung; Regionale Entwicklung; Deutschland